Production of Ultrathin and High-Quality Nanosheet Networks via Layer-by-Layer Assembly at Liquid-Liquid Interfaces - Coleman, Jonathan; Carey, Tian (My University, 2024)
Solution-processable 2D materials are promising candidates for a range of printed electronics applications. Yet maximizing their potential requires solution-phase processing of nanosheets into high-quality networks with carrier mobility (μNet) as close as possible to that of individual nanosheets (μNS). In practice, the presence of internanosheet junctions generally limits electronic conduction, such that the ratio of junction resistance (RJ) to nanosheet resistance (RNS), determines the network mobility via μNS/μNet ≈ RJ/RNS + 1. Hence, achieving RJ/RNS < 1 is a crucial step for implementation of 2D materials in printed electronics applications. In this work, we utilize an advanced liquid-interface deposition process to maximize nanosheet alignment and network uniformity, thus reducing RJ. We demonstrate the approach using graphene and MoS2 as model materials, achieving low RJ/RNS values of 0.5 and 0.2, respectively. The resultant graphene networks show a high conductivity of σNet = 5 × 104 S/m while our semiconducting MoS2 networks demonstrate record mobility of μNet = 30 cm2/(V s), both at extremely low network thickness (tNet < 10 nm). Finally, we show that the deposition process is compatible with nonlayered quasi-2D materials such as silver nanosheets (AgNS), achieving network conductivity close to bulk silver for networks <100 nm-thick.
PUBLISHED
Cited by: 1; All Open Access, Green Open Access, Hybrid Gold Open Access
Keywords: Solution-processable 2D materials; nanosheets; internanosheet junction; printed electronics, self-assembly, nanoplatelets, device, transistor, charge transport